Anorexia nervosa, depression and medicalisation: a corpus-based study of patients and professionals - Hunt, Daniel (2013)
This study reports on the analysis of the Mental Health Discourse Corpus. This dataset is comprised of four sub-corpora that contain patients' online discussions of anorexia nervosa, patients' online discussions of depression, general practitioners' discussions of anorexia, and general practitioners' discussions of depression, respectively. The methodology integrates quantitative corpus linguistic approaches with qualitative analysis drawing on Hallidayan functional grammar, discourse analysis and discursive psychology. By interrogating corpora of health communication across communicative modes and participants, the study offers novel insights into the verbal presentation of anorexia and depression by patients and professionals, and examines their respective uptake of medical explanations of mental illness.